A PEGylated fibrin hydrogel‐based antimicrobial wound dressing controls infection without impeding wound healing. Issue 6 (2nd August 2017) - Gil, Joel; Natesan, Shanmugasundaram; Li, Jie; Valdes, Jose; Harding, Andrew; Solis, Michael; Davis, Stephen C.; Christy, Robert J.
Abstract: Combat injuries are associated with a high incidence of infection, and there is a continuing need for improved approaches to control infection and promote wound healing. Due to the possible local and systemic adverse effects of standard 1% cream formulation (Silvadene), we had previously developed a polyethylene glycol (PEGylated) fibrin hydrogel (FPEG)‐based wound dressing for the controlled delivery of silver sulfadiazine (SSD) entrapped in chitosan microspheres (CSM). In this study, we have evaluated the antimicrobial and wound healing efficacy of SSD‐CSM‐FPEG using a full‐thickness porcine wound infected with Pseudomonas aeruginosa . Infected wounds treated with a one‐time application of the SSD‐CSM‐FPEG wound dressing demonstrated significantly reduced bacterial bioburden over time (99·99% of reduction by day 11; P < 0·05) compared with all the other treatment groups. The epithelial thickness and granulation of the wound bed was significantly better on day 7 (150·9 ± 13·12 µm), when compared with other treatment groups. Overall, our findings demonstrate that the SSD‐CSM‐FPEG wound dressing effectively controls P. aeruginosa infection and promotes wound healing by providing a favourable environment that induces neovascularisation. Collectively, sustained release of SSD using fibrin hydrogel exhibited enhanced benefits when compared with the currently available SSD treatment, and this may have significant implications in the bacterial reduction of infected wounds in military and civilian populations.